Competency of agriculture graduates in Malaysian public Universities - Marinah Muhammad; Ahmad Anwar Mohamed Ismail; Aweng Eh Rak (2013)
Graduates are a valuable asset for the country as they are the heirs who will continue the development of the country and is the source of human capital. This important resource must be developed through a good education system so as to produce quality and knowledgeable human capital for the country. A study was conducted to obtain the true picture of public perception with regard to agricultural graduates’ competency in Malaysia and what are the factors that influenced the competencies among them. The study was conducted in seven public universities and twenty companies in the plantation industry through the distribution of questionnaires to the students of agriculture and interviews with top management in the industry. The results shows that, career opportunities in the farming and commercial agricultural sector in Malaysia is bright and according to the industry, the agricultural graduates in Malaysia are competent, however, there are some aspects that need to be improved. Curriculums in universities also play an important role to make sure the students will be competent after graduation with other values inculcated in them during their studies in the University. The majority of these students pursuing agriculture program in the university are of their own initiative and awareness, without coercion from any party. This is a positive finding which goes to shows that, there are still many young people who are interested in agriculture. The often heard claims that, agriculture is not a favored field for the youth is not accurate anymore. These students also have the desired characteristics as expected by government to further develop the farming and commercial agricultural sector in Malaysia. However the percentage of the students who are willing to venture into the agriculture sector as wage earners or selfemployed after graduation, is still low. The findings of this study have also led to a further study on to two more aspect which are perceptions of agriculture students on a career in agriculture and the status of career opportunities in the plantation industry and commercial agriculture in Malaysia